THE INFLUENCE OF THE PLAYING LOAD ON THE FUNCTIONAL STATUS OF PROFESSIONAL FOOTBALL PLAYERS - Pavlichenko, P. (World of Medicine and Biology, 2014)
Background. Searching for the simple and minimally invasive methods for the diagnostics of the functional status in top levels footballers has always been a matter of interest in sports medicine and physiology. Considerable physical and psychological loads can cause the changes of the functional status and can lead to overloading processes and associated disturbances. Assessment of functional status of football players is aimed at optimization of training loads and improvement of physical performance, as well as at prevention of overloading processes and disturbances. Recently, assessment of variations in terminal part of T-wave, as detected by conventional electrocardiography, has been proposed as a simple index to monitor the functional status, that is, the individual athlete response to a given training load. Purpose. Estimation of changing of functional status of professional football players under the influence of playing loads. Methods. We used “Phazagraf” device for conducting our research. The method we used is based on comparison of ascending and descending parts of the T-wave of standard ECG, supplemented by measuring heart rate variability in order to assess the efforts of the vegetative nervous system and regulation systems of the body. The study involved thirty seven professional football players, aged 20-21, who had been candidates for the Ukrainian national under 21 football team and who had played for professional clubs of Ukrainian Premier League. The research was conducted as follows: Research 1 - performed before the match with Italy team, Research 2 – performed 2-hours after the end of the match with Italy team, Research 3 – performed at the end of the competitive period, basic data, Research 4 – performed at the same period as at Research 3, but on the next day after the match with Slovenia team. The investigation was carried out under standard conditions of basal metabolic rate (BMR), except research 2, which was conducted after the match. The main measuring indices included heart rate, βТ -index of symmetry of T-wave in standard ECG, effort index by Baevskiy. We performed also the analysis of functional status in players with different football specializations such as goalkeepers, forwards, defenders and mildfields. Results. The findings showed considerable changes of indexes after the football match: increasing of the heart rates, evaluation of the Baevskiy` effort index, increasing the βТ -index of T-wave symmetry. These changes hadn`t been normalized 2 hours after the match. Comparison of changes of functional status in footballers of different football specialization showed no differences. The next stage of our research showed prolonged effect of the playing loads. We found next day after the match that heart rates increased with statistical tendency (P